Regulation of the Discoidin I gamma gene in Dictyostelium discoideum: identification of individual promoter elements mediating induction of transcription and repression by cyclic AMP. - Vauti, F (1990)
We dissected the promoter of the developmentally induced and cyclic AMP-repressed discoidin I gamma gene and identified a sequence element essential for developmental induction. Transfer of the element to an inactive heterologous promoter demonstrated that this sequence is sufficient to confer expression in axenically growing cells and to induce gene activity in development after growth on bacteria. A 16-base-pair sequence within this element was shown to be sufficient for induction in the discoidin promoter context and was used to reactivate different truncated promoter constructs. This led to the localization of an element necessary for down regulation of gene expression by extracellular cyclic AMP.